2018
DOI: 10.1111/exd.13743
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive analysis and minimally invasive in vivo experimental challenges of the skin barrier

Abstract: In this review, we aim to give a concise and selective overview of noninvasive biophysical analysis techniques for skin barrier analysis (transepidermal water loss, electrical methods, confocal Raman microspectroscopy, sebumeter, reflectance spectrophotometry, tristimulus colorimetry, diffuse reflectance spectroscopy and reflectance confocal microscopy), including advantages and limitations. Rather than giving an exhaustive description of the many techniques currently available, we show the usefulness of a rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Skin measurement tools were extracted by literature search and by exploring their PubMed MeSH-terms. 4,[22][23][24][25]28 We defined 'noninvasive' as every method that theoretically cannot lead to skin irritation, bleeding or scarring; this excluded biopsies, epilation of eyelashes/hairs, application of tape or glue onto the skin, and collection of skin scrapings or excretions from sebaceous follicles. Only studies involving adult patients with cutaneous facial rosacea were included (Table S1; see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Skin measurement tools were extracted by literature search and by exploring their PubMed MeSH-terms. 4,[22][23][24][25]28 We defined 'noninvasive' as every method that theoretically cannot lead to skin irritation, bleeding or scarring; this excluded biopsies, epilation of eyelashes/hairs, application of tape or glue onto the skin, and collection of skin scrapings or excretions from sebaceous follicles. Only studies involving adult patients with cutaneous facial rosacea were included (Table S1; see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Of all imaging tools, RCM is superior for noninvasive skin thickness measurements. Possible alternatives are high-frequency ultrasound, near-infrared spectroscopy, optical coherence tomography, or Raman spectroscopy; however, these devices have lower resolution and are also expensive [17,[37][38][39]. Moreover, they may not all be suitable for facial imaging due to their size (e.g., Raman spectroscopy).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to water content and TEWL, other skin parameters may influence skin barrier function, such as natural moisturizing factor (NMF), SC thickness, dermal vasodilatation (erythema), intracellular lipids, and pH [2,4,15]. A wide array of noninvasive biophysical and imaging methods are available to assess most of these parameters [17]. In the current pilot study, we demonstrate the feasibility of combining a quartet of biophysical/imaging devices to measure the following four skin parameters noninvasively: erythema, TEWL, water content, and epidermal thickness.…”
Section: Introductionmentioning
confidence: 99%
“…50 µm in depths, at red/infrared excitation, i.e. it is well suited for non-invasive measurements of the entire SC in vivo [15]. A recent in vivo study using CRM confirmed the non-homogeneous distribution of lateral packing order of ICL, showing the prevalence of the orthorhombic phase in the depth of approx.…”
mentioning
confidence: 93%